PENGANGKATAN ANAK WARGA NEGARA INDONESIA YANG DIADOPSI OLEH WARGA NEGARA ASING (STUDI PENETAPAN PN NOMOR 1028/PDT.P/2007/PN.SBY DAN PENETAPAN PN NOMOR 62/PDT.P/2010/PN.MKD) - HARIADI SYAHPUTRA (PREMISE LAW JURNAL, 2017)
Adopting an Indonesian child by foreign citizens has to comply with the regulation in PP No. 54/2007 on the Implementation of Adopting a Child and the Decree of the Minister of Social Affairs No. 110/HUK/2009 on the Requirements for Adopting a Child through the Court’s Verdict. There are two types of legal protection for an Indonesian child adopted by foreign citizens in Indonesia – preventive and repressive. The District Court’s Verdict No. 1028/Pdt.P/2007/PN.Sby is in accordance with the constituents found in the Supreme Court’s Circular Letter No. 6/1983 on the Improvement of SEMA No. 2/1979 on Child Adoption, and the District Court’s Verdict No. 62/Pdt.P/2010/PN.Mkd is also appropriate since it does not meet the constituents in Article 13, letter e in conjunction with Article 16 and Article 14 of PP No. 54/2007 on the Implementation of Adopting a Child which explains that the adoptive parents-to-be have not married yet, and adopting a child by a single parent can only be done by an Indonesian citizen. Therefore, in their legal considerations, the judges have handed down the verdicts accurately.Keywords: Child Adoption, Indonesian Citizen, Foreign Citizen.